Analisis Dampak Kebijakan Alokasi Anggaran untuk Sektor Pariwisata Massal terhadap Manajemen Pariwisata Berkelanjutan di Destinasi Wisata Kampung Pelangi 200 di Kota Bandung - Dadan Ramdani (MASALIQ, 2025)
The significant growth of Indonesia’s tourism sector in recent years, including the development of community-based mass tourism destinations, underscores the need to evaluate the effectiveness of government budget allocations in supporting sustainability principles. This study aims to analyze the impact of government budget allocation policies on the management of sustainable tourism at the Kampung Pelangi 200 tourist destination in Bandung City. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and document analysis. The findings indicate that budget allocations directed toward infrastructure development, environmental sanitation, and community engagement have had a positive impact on the destination’s visual appeal, visitor comfort, and local economic growth, particularly in the MSME sector. Kampung Pelangi 200 has successfully become a clean, aesthetically appealing, and inclusive tourist destination through a collaborative approach involving local government, the community, and business actors. This success highlights the importance of structured budget management that is responsive to local needs and oriented toward environmental and social sustainability. The study concludes that budget policies focused on participatory and sustainable aspects can serve as a foundation for an inclusive and competitive tourism management model. The implications call for the strengthening of public policies that ensure equitable distribution of tourism benefits and the long-term viability of community-based destination development.